2022
DOI: 10.3390/v14071547
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Functional Mx1 Protein Is Essential for the Ability of RIG-I Agonist Prophylaxis to Provide Potent and Long-Lasting Protection in a Mouse Model of Influenza A Virus Infection

Abstract: RIG-I is an innate sensor of RNA virus infection and its activation induces interferon-stimulated genes (ISGs). In vitro studies using human cells have demonstrated the ability of synthetic RIG-I agonists (3pRNA) to inhibit IAV replication. However, in mouse models of IAV the effectiveness of 3pRNA reported to date differs markedly between studies. Myxoma resistance (Mx)1 is an ISG protein which mediates potent anti-IAV activity, however most inbred mouse strains do not express a functional Mx1. Herein, we uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
(104 reference statements)
0
2
0
Order By: Relevance
“…Recently, Horman et al reported induction of ferret IFITM1, 2 and 3 in vitro in response to treatment of cells with ferret IFN-α or infection with IAV 44 , although these studies did not investigate induction in vivo, cellular localisation or the antiviral activity of the different ferret IFITMs. Further studies characterising similarities and differences between restriction factors expressed by humans and ferrets are of particular importance given the widespread use of ferrets as animal models to study IAV and other human respiratory virus infections, and of new prophylactic and therapeutic approaches that are based on activation of innate immune receptors such as RIG-I 1 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Horman et al reported induction of ferret IFITM1, 2 and 3 in vitro in response to treatment of cells with ferret IFN-α or infection with IAV 44 , although these studies did not investigate induction in vivo, cellular localisation or the antiviral activity of the different ferret IFITMs. Further studies characterising similarities and differences between restriction factors expressed by humans and ferrets are of particular importance given the widespread use of ferrets as animal models to study IAV and other human respiratory virus infections, and of new prophylactic and therapeutic approaches that are based on activation of innate immune receptors such as RIG-I 1 4 .…”
Section: Discussionmentioning
confidence: 99%
“…As first line of defence, highly conserved cell -associated innate immune sensing receptors such as the cytoplasmic helicase RIG-I can detect viruses, specifically viral nucleic acids, triggering a signalling cascade that results in the rapid induction of diverse antiviral effectors. In our previous work we have demonstrated that the activation of those pathways with synthetic RNA ligands of RIG-I provides potent protection from viral infection with influenza A virus (IAV), severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and respiratory syncytial virus (RSV) in mice and ferrets 1 4 . Cell-intrinsic innate antiviral defences include a range of intracellular proteins with antiviral activity that are regulated independently of interferons (IFNs), as well as IFN stimulating genes (ISGs).…”
Section: Introductionmentioning
confidence: 99%